Advancing Tropical Medicine: Interdisciplinary Approaches, Innovation, and Health System Strengthening - Satish Kumar Sarankar; Sushma Somkuwar (International Journal of Tropical Medicines, 2024)
Tropical medicine encompasses a diverse range of infectious diseases prevalent in tropical and subtropical regions, presenting complex challenges to global health. This review offers an extensive examination of critical aspects within tropical medicine, emphasizing recent progress and upcoming avenues of research. Interdisciplinary collaboration is highlighted as essential for addressing the multifaceted nature of tropical diseases, with healthcare professionals, veterinarians, ecologists, epidemiologists, and social scientists working together to tackle complex health challenges. Innovation in diagnostics and therapeutics, including the development of rapid diagnostic tests and novel treatment strategies, is crucial for improving disease surveillance, case management, and outbreak response. Vector control and environmental management strategies, integrated within the framework of One Health approaches, play a pivotal role in reducing the burden of vector-borne diseases in tropical regions. Additionally, strengthening health systems through infrastructure development, workforce capacity building, and research translation is imperative for improving access to quality healthcare and public health services. By addressing these key areas and investing in collaborative research and intervention efforts, we can advance the prevention, control, and management of tropical diseases and improve health outcomes for populations in tropical regions and beyond.
Keywords: Tropical diseases; Vector control; antimicrobial resistance; epidemiology; global health; infectious diseases